Viral transmission, neuropathogenesis and therapeutic antibody studies in a murine model of enterovirus 71 encephalomyelitis / Tan Soon Hao - Tan, Soon Hao (2017)
Enterovirus A71 (EV-A71), a single, positive-stranded RNA virus, belongs to the Picornaviridae family within the Enterovirus genus. Rarely, EV-A71 could lead to severe neurological complications such as aseptic meningitis, encephalitis and poliomyelitis-like acute flaccid paralysis. Patients with fatal brainstem encephalitis usually die within a few hours after hospital admission due to sudden cardiopulmonary arrest. The objectives of this project were to investigate various aspects of viral transmission, neuropathogenesis and effectiveness of therapeutic antibodies in a murine model of EV-A71 encephalomyelitis. EV-A71 retrograde axonal transport up peripheral spinal nerves has been previously reported. However, whether EV-A71 could use retrograde axonal transport up cranial nerves to enter the brainstem remains unknown. To investigate this, mouse-adapted-virus-strain (MAVS) was injected into unilateral jaw/facial muscles of groups of mice. Infected mice were sacrificed at several time points for pathological (H&E, immunohistochemistry and in situ hybridisation) and viral titration analysis. Viral antigens/RNA were visualised within the cranial nerves and brainstem (motor-related region), ipsilateral to the injection site. Brainstem viral titres were also significantly higher than spinal cord titres at early time point. The distribution of neuronal infection in human or mouse brain was distinct and rather stereotyped. This could be due to the variable susceptibility of different neurons to EV-A71 infection, or related to virus entry routes into the CNS. To study this, 2 groups of mice were intra-cerebrally (thalamus/hypothalamus or pons/medulla) inoculated with MAVS. Infected mice were sacrificed at various time points for pathological and viral titration analysis. In addition, a primary motor neuron cell was also prepared from E14 mouse spinal cord to study the permissiveness of mouse motor iv neuron to MAVS infection. Based on the results, MAVS was not found to be replicating extensively in the brain or primary motor neuron cells. Skeletal muscle injury has been shown to facilitate poliovirus retrograde axonal transport and subsequently enhances viral invasion into the CNS. To study the possibility of involvement of this important paralytic risk factor in EV-A71 infection, groups of mice with muscle-traumatised or non-traumatised hindlimb were intraperitoneally-infected with MAVS. Both groups of mice did not show significant differences in viral antigens/RNA and viral titres in hindlimb muscles and spinal cords. To date, neither licenced vaccines nor therapeutic drugs were available to prevent or treat EV-A71 patients with CNS manifestations. A mouse IgM MAb was previously developed and showed cross-neutralisation of EV-A71 strains with genotypes B3-B5, and C1-C5. With an optimum dose of MAb given after MAVS CNS infection, a reduction of disease severity (reduced viral antigens/RNA and viral titres in the CNS) and mortality were observed in treated mice. In conclusion, MAVS could utilise cranial nerves to achieve brainstem infection via retrograde axonal transport. The stereotype distribution of neuronal infection was more likely due to viral entry routes but not due to differences in neuron susceptibility. Skeletal muscle injury did not enhance the retrograde axonal transport of MAVS. Mouse monoclonal antibody was useful in preventing and ameliorating CNS infection.